The relation of feathering and overflow fat of lamb carcasses to the grade of the lamb, degree of marbling, and market value of the lamb. - Mackintosh, D.L.; Merkel, R.A.; Menzies, C.S.; Kropf, Donald H.; Forrest, J.C. (Kansas Agricultural Experiment Station, 2011)
A total of 279 crossbred lambs were slaughtered over a three-year period at an approximate live weight of 90 pounds. USDA carcass grade and the various quality factors influencing grade were scored by a representative of the Federal Grading Service. The rack was dissected into fat, lean, bone, overflow and intercostal muscle. The longissmus dorsi and intercostals muscle were removed for fat analyses by the Modified Babcock Method. Color was determined in the longissimus dorsi and rectus abdominis with a Photovolt Reflectance Colormimeter. Loin samples were used for taste panel evaluations. Myoglobin concentration, by the Poel Cyano Method, pH, and expressible moisture, by the filter paper method, were also determined in the longissmus dorsi, rectus abdominals, and intercostals muscles.
Keywords: Meat; Rib feathering; Fat; Market value